1998
DOI: 10.1002/(sici)1099-0844(1998120)16:4<261::aid-cbf796>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative activity in mitochondria isolated from rat liver at different stages of development

Abstract: The purpose of this study was to evaluate the oxidative capacities in hepatic mitochondria isolated from prepubertal, young adult and adult rats (40, 90 and 180 days of age, respectively). In these rats, mitochondrial respiratory rates using FAD- and NAD-linked substrates as well as mitochondrial protein mass were measured. The results show that only the oxidative capacity of FAD-linked pathways significantly declined in mitochondria from 180-day-old rats compared with those from younger animals. When we consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…Maximal oxygen consumption rates were measured in homogenates and isolated mitochondria polarographically with a Clark-type electrode (Yellow Springs Instruments, Yellow Springs, Ohio), maintained in a water-jacketed chamber at 30°C, as previously reported [16]. Briefly, aliquots of homogenates and isolated mitochondria were incubated in 3 ml of the above suspension medium and were allowed to oxidise their endogenous substrates for a few minutes.…”
Section: Measurement Of Respiration In Liver Homogenates and Mitochonsupporting
confidence: 58%
“…Maximal oxygen consumption rates were measured in homogenates and isolated mitochondria polarographically with a Clark-type electrode (Yellow Springs Instruments, Yellow Springs, Ohio), maintained in a water-jacketed chamber at 30°C, as previously reported [16]. Briefly, aliquots of homogenates and isolated mitochondria were incubated in 3 ml of the above suspension medium and were allowed to oxidise their endogenous substrates for a few minutes.…”
Section: Measurement Of Respiration In Liver Homogenates and Mitochonsupporting
confidence: 58%
“…We have previously found that a decrease in FAD-linked respiration is the first age-linked biochemical impairment of energy-transducing pathways which could be detected in liver mitochondria from 180-day-old rats [3,4]. This finding is in line with other results in which tissue ageing is associated with a decrease in electron transport chain enzyme activity [5].…”
Section: Cmls Cellular and Molecular Life Sciencessupporting
confidence: 81%
“…In this work, we found that the decline in succinate-supported state 3 respiration previously observed in adult rats [3,4] is due to a decrease in COX activity and ANT content. COX activity and ANT are known to exert a strong control over liver respiration [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation